KARAKTERISTIK PADA ANAK DOWN SINDROM DI SLB NEGRI PEMBINA MEDAN - ADINDA .; ISRA THRISTY (JURNAL ILMIAH SIMANTEK, 2021)
Down syndrome is a genetic disorder caused by chromosomal abrasion which causes the baby to have an excess of 1chromosome on chromosome 21, can be recognized by specific physical signs, IQ intelligence level is below normal andbelongs to the group of mental retardation. This type of research is quantitative descriptive with a cross sectional design,data collection is taken once, to determine the characteristics of children with Down syndrome at SLB E Negri PembinaMedan. The highest proportion of Down Syndrome children based on the sociodemography of Down Syndrome childrenaged 6-10 years (63%), based on male sex 11 people (40.7%), based on education level 27 elementary school students(100%), based on Most children diagnosed with Down syndrome were after birth as many as 25 people (92.6%), based onfamily ancestry without previous Down syndrome as many as 24 people (88.9%), Clinical symptoms that often appear inchildren with Down syndrome are slanted eyes, ears small and low position, short neck, short fingers and toes, 2 finger littlefinger, wide thumb and forefinger distance of 27 people (100%). Children with down syndrome are mostly affected by themale sex. male, aged 6-10 years, with elementary school education, many children with Down syndrome are diagnosed afterbirth, and do not have children in the family.